OPTIMIZATION DESIGN OF POLYGONAL THIN-WALLED TUBES STRUCTURE WITH INDUCED IMPERFECTION - MA ShaoLin; MIAO FuXing (Jixie qiangdu)
In this paper,the finite element method was used to simulate the thin-walled structure under axial impact. The influence of the cross-sectional shape and induced hole size of the thin-walled tube on deformation mode of structure and energy absorption capacity were analyzed. The results show that the impact force on the edge of the thin-walled tube is larger,as the number of sides of the section increases within a certain range,the parameters of the energy absorption index of the regular polygon and the star-shaped polygonal thin-walled tube are increasing. The initial peak force of the thin-walled tube with induced imperfection is reduced by 50% compared to the previous one. If the length of the thin-walled tube with induced imperfection is constant,as the width decreases,the energy absorption,average compressive force and specific energy absorption of the thinwalled tube gradually increase. The finite element analysis results were combined with the response surface method to optimize the design of thin-walled tubes with induced imperfection,and preliminary data and analysis results were provided for the optimal design of induced thin-walled energy-absorbing structures.